Знак Креста: роман, очерки, публицистика / Б. К. Зайцев - Зайцев Борис Константинович (Репро, 2009)
Экземпляры: БС (20170901) / Инвентарный номер: РТШ51840 / Сис.шифр: Р2 / Авт.знак: З-17 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-4